PENGEMBANGAN POTENSI WAKAF DI MASJID AT TAQWA BINUANG KAB TAPIN - Aisyah, Lisda (Islamic Economics and Business Faculty of UIN Antasari, 2018)
Waqaf besides has spiritual values also has social economic values. Indonesia has the potential endowments are very boast. If the potential of waqf is well developed, then it will give good effect to the economy of the society and welfare. Endowments can be effective and have the maximum benefits if developed, one of which is through a change in the understanding of the concept of endowments consumptive become productive. The development of this potensial will make change in society?s views and goal in terms of the development of Muslims.